Biallelic variants in ZFP36L2 cause female infertility characterised by recurrent preimplantation embryo arrest. Issue 9 (5th October 2021) - Zheng, Wei; Sha, Qian-Qian; Hu, Huiling; Meng, Fei; Zhou, Qinwei; Chen, Xueqin; Zhang, Shuoping; Gu, Yifan; Yan, Xian; Zhao, Lei; Zong, Yurong; Hu, Liang; et al.
Abstract : Background: Recurrent preimplantation embryo developmental arrest (RPEA) is the most common cause of assisted reproductive technology treatment failure associated with identified genetic abnormalities. Variants in known maternal genes can only account for 20%–30% of these cases. The underlying genetic causes for the other affected individuals remain unknown. Methods: Whole exome sequencing was performed for 100 independent infertile females that experienced RPEA. Functional characterisations of the identified candidate disease-causative variants were validated by Sanger sequencing, bioinformatics and in vitro functional analyses, and single-cell RNA sequencing of zygotes. Results: Biallelic variants in ZFP36L2 were associated with RPEA and the recurrent variant (p.Ser308_Ser310del) prevented maternal mRNA decay in zygotes and HeLa cells. Conclusion: These findings emphasise the relevance of the relationship between maternal mRNA decay and human preimplantation embryo development and highlight a novel gene potentially responsible for RPEA, which may facilitate genetic diagnoses.